Kajian Jumlah Sel Limfosit Pasca Vaksinasi Covid-19 Dosis Tiga dengan Metode Diff CountKajian Jumlah Sel Limfosit Pasca Vaksinasi Covid-19 Dosis Tiga Dengan Metode Diff Count - Asri Jumadewi; Irwana Wahab; Nazir Nazir; Halimatussakdiah Halimatussakdiah (FORIKES, 2023)
The number of lymphocyte cells is one indicator of the body's immunity. Vaccination is carried out to increase immunity against COVID-19 disease. Injecting the third dose of the COVID-19 vaccine is expected to increase the lymphocyte cell count. This study aims to investigate the increase in the number of lymphocytes after the third stage of COVID-19 vaccination in adolescents. The research design applied in this study was cross-sectional. This study involved a sample of 80 adolescents, based on inclusion criteria, with a sampling technique that was purposive sampling. This research was conducted at the Department of Medical Laboratory Technology, Poltekkes Kemenkes Aceh, in September 2022. The blood samples obtained were then processed and analyzed using descriptive statistical methods. The results showed that there was an increase in the number of lymphocytes by 46.25%, the number of normal lymphocytes was 40%, and the number of lymphocytes decreased by 13.75% with an average value of 36.89% and a standard deviation of 12.68. It was concluded that the number of lymphocyte cells increased in respondents due to the third phase of the COVID-19 vaccine. This increase is expected to provide herd immunity against the spread of COVID-19 which has hit since 2019.Keywords: COVID-19; vaccination; lymphocyte count; diffcount; herd immunity ABSTRAK Jumlah sel limfosit merupakan salah satu indikator imunitas tubuh. Vaksinasi dilakukan untuk meningkatkan imunitas terhadap penyakit COVID-19. Penyuntikan vaksin COVID-19 dosis ketiga diperkirakan dapat meningkatkan limfosit cell count. Penelitian ini bertujuan untuk menginvestigasi peningkatan jumlah limfosit setelah vaksinasi COVID-19 tahap ketiga pada usia remaja. Desain penelitian yang diterapkan dalam studi ini adalah cross-sectional. Penelitian ini melibatkan sampel dari 80 remaja, berdasarkan kriteria inklusi, dengan teknik pengambilan sampel yaitu purposive sampling. Penelitian ini dilakukan di Jurusan Teknologi Laboratorium Medik, Poltekkes Kemenkes Aceh, pada pada bulan September tahun 2022. Sampel darah yang didapatkan selanjutnya diolah dan dianalisis menggunakan metode statistik deskriptif. Hasil penelitian menunjukkan bahwa terjadi peningkatan jumlah limfosit sebanyak 46,25%, jumlah limfosit normal sebanyak 40%, dan jumlah limfosit menurun sebanyak 13,75% dengan nilai rata-rata sebesar 36,89% dan deviasi standar 12,68. Disimpulkan bahwa jumlah sel limfosit meningkat pada responden akibat pemberian vaksin COVID-19 tahap ketiga. Peningkatan ini diharapkan dapat menjadi herd immunity terhadap penyebaran COVID-19 yang telah melanda semenjak tahun 2019 lalu.Kata kunci: COVID-19; vaksinasi; jumlah limfosit; diff count; herd immunity